Follicular T cells and the control of IgE responses - Pablo F. Cañete; Di Yu (Allergology International)
Atopy is considered the epidemic of the 21st century, and while decades of research have established a direct link between Th2 cells driving pathogenic IgE-mediated allergic disease, only in the past years have T follicular helper (Tfh) cells emerged as pivotal drivers of these responses. In this review, we will examine the molecular mechanisms governing the IgE response, with a particular emphasis on the key cytokines and signaling pathways. We will discuss the exclusion of IgE-producing B cells from germinal centers and explore the recently established role of follicular T cell function and heterogeneity in driving or curtailing these immune responses. Additionally, we will assess the current state of major monoclonal antibodies and allergen immunotherapies designed to counteract Th2-driven inflammation, as well as reflect on the need to investigate how these biologics impact Tfh cell activity, differentiation, and function, as these insights could pave the way for much-needed therapeutic innovation in the treatment of allergic diseases.